Comparison of Discovery Learning and Reciprocal Teaching Learning Models on the Mathematical Critical Thinking - Sofhianti Ardini; Srie Kuntari (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Mathematical critical thinking ability is a very important ability and must be possessed by students. This study aims to compare discovery learning and reciprocal teaching models on students' mathematical critical thinking skills. This research was conducted on VIII grade students of MTs Ma'arif NU 1 Wangon with a sample of VIII A and VIII D classes totaling 68 students. The sampling technique used simple random sampling where the sampling process was taken in a simple event with a lottery. The research was conducted by giving two different treatments to two classes, experimental class I with discovery learning model and experiment II with reciprocal teaching model. The research method used is quasi experimental design. While the data collection method uses tests in the form of pretest and posttest description questions. Data analysis techniques are using normality test, homogeneity test and hypothesis testing. The average posttest result in experimental class I is 81.3 which is in the very high category and the average posttest result in experimental class II is 73.4 which is in the medium category. Based on the analysis of the t test of two independent samples, the significance value is 0.000 which is smaller than the level limit of 0.05. So it can be concluded that the results of this study show that there is a significant difference in the ability to think critically mate. Keywords: Comparison, Discovery learning, Mathematical Critical Thinking Skills, Reciprocal Teaching.